(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In our days one of the actual problems is the return/inculcation of a hijab as a religious marker in Kazakhstan’s space. Therefore, this article’s purpose is to research the features of the formation of women’s religious identity, namely, the study of the reasons for women’s acceptance of a veiled Muslim woman’s life way, and also to analyze the changes that have occurred in the lives of Muslim women after conversion to Islam. The article analyzed the works of Kazakh, Russian and foreign scientists who researched the problem of female religiosity. In order to research modern situation the interview with veiled Muslim women was conducted. In the course of the study, we came to the conclusion that modern Muslim women are active, versatile personalities who view hijab as a symbol of religious obedience, freedom of individual choice, protest and heroism. In general, the provided research gave an opportunity to consider the process of formation religious identity of Muslim women from actor’s position using the biographical method. Therefore, the obtained results can be used in further development of the problem under consideration, as well as in preparing a lecture for students of sociological and religious studies. Key words: Islam, Muslim woman, hijab, feminism, religious identity.